Long‐term performance and lead failure analysis of the Durata defibrillation lead compared to its previous model, the recalled Riata defibrillation lead. (1st August 2019) - Kleemann, Thomas; Nonnenmacher, Florian; Strauss, Margit; Kouraki, Kleopatra; Werner, Nicolas; Fendt, Andràs; Zahn, Ralf
Abstract: Introduction: Data on long‐term durability of St Jude Medical Durata defibrillation leads compared to its previous model, the St Jude Medical Riata leads in clinical practice are missing. Aim of the study was to analyze the long‐term performance of the Durata defibrillation leads compared to the Riata leads in clinical practice. Methods and Results: A total of 1407 consecutive patients of a prospective single‐centre implantable cardioverter defibrillator (ICD)‐registry were analyzed who underwent ICD implantation with a Durata (n = 913) or Riata (n = 494) ICD lead between 2002 and 2017. Most of the leads were implanted via a subclavian vein access. The estimated lead defect rates after 5 and 10 years were not different between the Durata (11% and 36%) and Riata leads (13% and 38%). Among Durata leads single coil and DF‐4 connector ICD leads had a lower incidence of lead failure. Major causes of lead failure were compression of the lead in the clavicular region, generator to lead friction and distal fatigue fracture whereas lead defect due to externalization was a rare cause of lead defect in Riata leads (3%). Conclusion: Among ICD leads implanted via the subclavian vein access the lead defect rate of Durata leads after 10 years is similar to that of Riata leads. Single coil and DF‐4 ICD leads are associated with a lower lead failure rate. Mechanical stress represents a major cause of lead failure mechanism whereas externalization might only play a minor role in clinical practice.